Unmanned Spacecrafts and Space Drones as the Challenges for Space Law - Вишновецька, Світлана Василівна; Вишновецька, С. В.; Вишновецкая, Светлана Васильевна; Vyshnovetska, Svitlana V.; Мельник, Володимир Петрович; Мельник, В. П.; Мельник, Владимир Петрович; Melnyk, Volodymyr P. (ISPC, 2020)
In the article, the authors considered the challenges for space law, which are created by the intensive development of production technologies of unmanned spacecrafts and space drones, as well as their use in the space industry. The authors clarified the term “space object”, which is used in the Space Law. This helped reveal the difference between the terms “unmanned spacecrafts” and “space drones”, which are synonymous in the Air Law. The authors investigated the basics of the space law and proved that in the existing formulations, the space law is not able to regulate the modern space exploration. Based on the study, the authors proposed: 1) to consolidate the influence of public organizations created in the space industry and specializing in the space exploration in the space law; 2) to change approaches to space law; space law should be considered as an effective regulator capable of ensuring the sustainable development of the mankind; 3) under the space law, to create a holistic concept for using all types of space object on the Low Earth Orbit.

У статті автори розглянули проблеми космічного права, які виникають через інтенсивний розвиток технологій виробництва безпілотних космічних апаратів та космічних дронів, а також їх використанням у космічній галузі. Автори роз'яснили термін "космічний об'єкт", який використовується в космічному праві. Це допомогло виявити різницю між термінами "безпілотні космічні апарати" та "космічні дрони", які є синонімами в повітряному праві. Автори дослідили основи космічного права і довели, що в існуючих формулюваннях космічне право не здатне регулювати сучасне дослідження космосу. На підставі дослідження автори запропонували: 1) закріпити вплив громадських організацій, створених у космічній галузі та спеціалізуються на дослідженні космосу в космонавтиці; 2) змінити підходи до космічного права; космічне право слід розглядати як ефективний регулятор, здатний забезпечити сталий розвиток людства; 3) відповідно до закону про космос створити цілісну концепцію використання всіх типів космічних об’єктів на низькій навколоземній орбіті.

В статье авторы рассмотрели проблемы космического права, которые возникают в результате интенсивного развития технологий производства беспилотных космических аппаратов и космических дронов, а также их использования в космической отрасли. Авторы уточнили термин «космический объект», который используется в космическом праве. Это помогло выявить разницу между терминами «беспилотные космические аппараты» и «космические дроны», которые являются синонимами в воздушном праве. Авторы исследовали основы космического права и доказали, что в существующих формулировках космическое право не способно регулировать современное освоение космоса. По результатам исследования авторы предложили: 1) консолидировать влияние в космическом праве общественных организаций, созданных в космической отрасли и специализирующихся на освоении космоса; 2) изменить подходы к космическому праву; космическое право следует рассматривать как эффективный регулятор, способный обеспечить устойчивое развитие человечества; 3) создать в космическом праве целостную концепцию использования всех типов космических объектов на низкой околоземной орбите.
Vyshnovetska S. Unmanned Spacecrafts and Space Drones as the Challenges for Space Law / S. Vyshnovetska, V. Melnyk // Philosophy and Cosmology. – V. 24. – ISPC, 2020. – Р. 39-47.
Keywords: space object; unmanned spacecrafts; space law; space drones; U-space; air law; Low Earth Orbit; космічний об'єкт; безпілотні космічні апарати; космічне право; космічні дрони; U-космос; повітряне право; низька навколоземна орбіта; космический объект; беспилотные космические аппараты; космическое право; космические дроны; U-космос; воздушное право; низкая околоземная орбита; Research Subject Categories::LAW/JURISPRUDENCE